The impact of reducing and eliminating user fees on facility-based delivery: a controlled interrupted time series in Burkina Faso. Issue 8 (26th September 2018) - Nguyen, Hoa Thi; Zombré, David; Ridde, Valery; De Allegri, Manuela
Abstract: User fee reduction and removal policies have been the object of extensive research, but little rigorous evidence exists on their sustained effects in relation to use of delivery care services, and no evidence exists on the effects of partial reduction compared with full removal of user fees. We aimed to fill these knowledge gaps by assessing sustained effects of both partial reduction and complete removal of user fees on utilization of facility-based delivery. Our study took place in four districts in the Sahel region of Burkina Faso, where the national user fee reduction policy (SONU) launched in 2007 (lowering fees at point of use by 80%) co-existed with a user fee removal pilot launched in 2008. We used Health Management Information System data to construct a controlled interrupted time-series analysis and examine both immediate and sustained effects of SONU and the pilot from January 2004 to December 2014. We found that both SONU and the pilot led to a sustained increase in the use of facility-based delivery. SONU produced an accumulative increase of 31.4% ( P  < 0.01) over 8 years in the four study districts. The pilot further enhanced utilization and produced an additional increase of 23.2% ( P  < 0.001) over 6 years. These increasing trends did not continue to reach full coverage, i.e. ensuring that all women had a facility-based delivery. Instead, they stabilized 3 years and 4 years after the onset of SONU and the pilot, respectively. Our study provides further evidence that user fee reduction and removal policies are effective in increasing service use in the long term. However, they alone are not sufficient to achieve full coverage. This calls for the need to implement additional measures, targeting for instance geographical barriers and knowledge gaps, to achieve the target of all women delivering in the presence of a skilled attendant.